The experience of use of the sand art-therapy with children with autism spectrum disorders - Kotlovanova O.V; Malinina E.V (Moscow State University of Psychology and Education, 2015)
The article presents the results of effective work to use sand art-therapy for treatment of behavior problems in children with autism spectrum disorder. The article describes the session plan, children's behavior in dynamics and intermediate results of work with children with autism spectrum disorders in the framework of this program. The influence of the sand art-therapy on the children's behavior was analyzed. The clinical case of sessions with the boy K. was described. The overwhelmingly positive influence of such sessions was determined.